Implementing Lean Manufacturing to Optimize Service Level: An Industrial Lubricating Oils Processing and Marketing Company Case Study - Herrera Barberena, David Felipe (2024)
This research aims to implement a lean manufacturing management model using tools such as value stream mapping (VSM), single-minute exchange of die (SMED) and autonomous maintenance (AM) to improve the service level within petroleum refining companies. Moreover, its objective is to mitigate the technical gap that leads to monetary losses for the company in question. In terms of methodology, the research used a case study design focused on pre-test and post-test analyses to identify the key improvements. The results revealed a 35 % reduction in company losses and an increase of 19 % in the service level.